Personal Values as a Mediator of Relations Between Perceived Parental Support and Control and Youth Substance Use. (15th October 2017) - Borca, Gabriella; Rabaglietti, Emanuela; Roggero, Antonella; Keller, Peggy; Haak, Eric; Begotti, Tatiana
ABSTRACT: Background : Tobacco and marijuana smoking are very popular in adolescence and there is a high rate of comorbidity between them, even in young adulthood. Parental support and control may hinder involvement in the use of these substances by promoting conventional values among adolescents. Objectives : The present study investigates the relations between family functioning (parental support and control) and psychoactive substance use (tobacco and marijuana smoking) and determines whether these relationships are mediated by personal values (in terms of disapproval of deviance and beliefs about the importance of school, health and religion). Methods : 175 Italian late adolescents (17 to 20 years old) participated in this two-wave longitudinal study. Data were collected at school through an anonymous questionnaire. Results : Greater parental control and support were directly associated with lower adolescent tobacco and marijuana use; adolescent acceptance of conventional values mediated the association between parenting and adolescent marijuana use. Conclusion : Findings emphasize the influence of family relationships throughout adolescence. The transmission of conventional values to adolescents may be a critical mechanism through which parenting protects adolescents from substance use, especially marijuana use.